2015
DOI: 10.12912/23920629/60024
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in the Duration of the Meteorological Vegetation Period in Poland in the Years 1971–2000 and 1981–2010

Abstract: In this paper, changes in the duration of the meteorological vegetation period in Poland were analyzed for the three decade period: 1981-2010 as compared to the 1971-2000 period. The meteorological data regarding the monthly mean air temperature values from 53 weather stations distributed evenly across Poland were used. It was proved that the meteorological vegetation period in the years 1981-2010 increased by four days on average, as compared to the 1971-2000 period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Results of Nieróbca et al (2013) show a similar tendency. The increase in the length of the growing season in different regions of Poland was also confirmed by other authors, among others, Żmudzka and Dobrowolska (2001), Kożuchowski and Degirmendžić (2005), OlechnowiczBobrowska and Wojkowski (2006), Skowera and Kopeć (2008), Kijowska (2010), Krużel et al (2015), Tylkowski (2015) and Graczyk and Kundzewicz (2016). A similar trend of changes has also been observed in other temperate regions, inter alia, in Scandinavia and Finland (Carter 1998;Irannezhad and Kløve 2015) and China (Song et al 2009).…”
Section: Discussion and Summarysupporting
confidence: 75%
“…Results of Nieróbca et al (2013) show a similar tendency. The increase in the length of the growing season in different regions of Poland was also confirmed by other authors, among others, Żmudzka and Dobrowolska (2001), Kożuchowski and Degirmendžić (2005), OlechnowiczBobrowska and Wojkowski (2006), Skowera and Kopeć (2008), Kijowska (2010), Krużel et al (2015), Tylkowski (2015) and Graczyk and Kundzewicz (2016). A similar trend of changes has also been observed in other temperate regions, inter alia, in Scandinavia and Finland (Carter 1998;Irannezhad and Kløve 2015) and China (Song et al 2009).…”
Section: Discussion and Summarysupporting
confidence: 75%
“…As a result of this study, it was shown that the most intensive increase in the length of the growing season was recorded in north-western Poland, in particular in seaside stations, i.e., in Łeba (6.9 days/10 years) and Hel (6.8 days/10 years). The increase in the length of the growing season in different regions of Poland was also confirmed by other authors, among others, Skowera and Kopeć (2008), Żmudzka andDobrowolska (2001), Olechnowicz-Bobrowska andWojkowski (2006), Krużel et al (2015), Graczyk and Kundzewicz (2016). A similar trend was observed on the basis of different periods and methods also in other regions, including Scandinavia (Carter 1998), Germany Finland (Irannezhad andKløve 2015) and also in the western United States (Feng and Hu 2004) and China (Dong et al 2013).…”
Section: Summary and Discussionsupporting
confidence: 77%
“…The increasingly late ending of the meteorological growing season as the reason for extending its duration in the years 2001-2009 in relation to the years 1971-2000 was reported by Nieróbca et al (2013). Krużel et al (2015) stated that the average 4-day increase in the ◂ duration of this period in Poland is the result of both its starting 2 days earlier and ending 2 days later.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One of the research directions that climate warming has given rise to is the possibility of growing thermophilous plants in Poland, especially grapevines [30,31]. Other positive characteristics of warming include the prolongation of the meteorological growing period, indicated in numerous publications [32][33][34].…”
Section: Resultsmentioning
confidence: 99%